TEK PARTİ DÖNEMİNDEKİ BAZI DİNÎ YAYINLARIN YASAKLANMA SEBEPLERİ - (:unkn) unknown (My University, 2015)
Her  siyasî  anlayış,  kendi  kriterlerine  uygun  olmadığını  düşündüğü  bazı  gazete,  mecmua  ve  kitap  gibi  çeşitli  yayınları  yasaklamıştır.  Tek  partili  yıllarda  da  diğer  dönemlerde  olduğu  gibi  bazı  dinî  muhtevalı  yayınların  basımı,  iç  ve  dış  siyasete  uygun  görülmeyerek  engellenmiştir.  M.  Kemal   Atatürk   döneminde   daha   çok   dini   tahrif   edici   yayınlar   yasaklanırken;   İsmet   İnönü'lü  yıllarda  "dua  mecmuası"  ve  tek  parti  zihniyetini  eleştiren  kişilerin  eserleri  de  bu  tür  bir  akıbete  maruz   kalmıştır.   Kurucu   irade   bu   kararı   alırken   çoğu   zaman   Diyanet   İşleri   Reisliği'nin   konu  hakkındaki  fikrine  başvurmamıştır.  Mezkûr  dönemde  yasaklanan  yayınlarla  ilgili  kararnamelere  bakıldığında   ise,   pek   çok   eserin   Matbuat   Kanunu'nun   yanlış   maddesi   ile   memnu   kılındığı   an---laşılmaktadır.

The  Reasons  of  Prohibition  of  Some  Religious  Publications  in  the  Single  Party  Era  Every  political  understanding  prohibited  some  publications  such  as  newspapers,  maga---zines  and  books  because  it  perceived  them  as  opposite  to  its  criteria.  Even  during  the  single  party  years,   which   were   the   same   as   other   terms,   some   religious   publications   were   inhibited   from  publication  by  the  politicians  because  of  not  being  suitable  for  domestic  and  international  political   views. ?hen the publications distorting religion were banned in the M Kemal Ataturk's era, both "prayer magazine" and works written by those criticizedthe single---party mentality were under the same prohibition in the smet nonu's years. ?enerally, founding will did not consult with the eadership of Religious Affairs about the issue banning in decision---making process. ?hen the degrees related to the banned publications were looked at, it is understood that many works were prohibited with a wrong article of the press law.
The Reasons of Prohibition of SomeReligious Publications in the Single Party Era
Keywords: Din Bilimi